The SuratKu Application as Electronic Mail Innovation in Supporting Governance at the Kulon Progo Regency Communication and Information Office - Ach. Apriyanto Romadhan; Switsa Cellindita; Iradhad Taqwa Sihidi; Asep Nurjaman; Muhammad Kamil (Sospol : Jurnal Sosial Politik, 2022)
This study focuses on the "SuratKu" electronic mail innovation made by the Kulon Progo Regency Communication and Information Office. The innovation aims to support good governance in the correspondence management process so that it is faster, more precise and accurate. This is a form of the bureaucratic digitilization process. Specifically, this paper tries to see how the developed information technology innovations can facilitate communication and coordination between government agencies/government to government in Kulon Progo Regency. The method used in this study is a qualitative research with a descriptive approach. Data collection techniques were carried out by observation, interviews and documentation. And for the results, the data was analyzed using an interactive data analysis model. The results showed that after going through various stages of testing and testing the feasibility of the SuratKu innovation, the implementation of the SuratKu innovation had run smoothly and was able to provide more effective and efficient mail administration services so that it could be adopted for implementation and use in all regional organizations.